Path planning and control of a mechatronic tricycle project - Yap, Zhiwei. (2009)
The aim for this project is to implementing a cheap and flexible positioning system. Bluetooth wireless technology has been chosen for this project. The reasons for choosing Bluetooth wireless technology is its low cost, low power consumption, open standard and ease of implementation.